ENVIRONMENTAL POLLUTANTS IN ORGANIC FARMING AND ORGANIC FOOD (International Journal of Food and Nutritional Sciences, 2021)
In current world scenario organic farming is a famous agricultural practice and covering a total area of approximately 71.5 Mha worldwide. Due to the involvement of certain practices in organic farming, food safety and human health is threatened by the flows of various environmental pollutants. Persistent organic pollutants, heavy metals, cyclodienes, organochlorine pesticides, hexachlorocyclohexanes, hexachlorobenzene, and nonbrominated flame retardants are some of the contaminants that occur in higher concentration in organic products. As a result, the lasting consumptions of organic products carrying such pollutants cause a considerable risk to human health. This present article decisively deal with the effect of organic farming on unknown and hidden threat due to the use of various composts as the nutrient and amendment sources that augment the phytoaccumulation and trophic transfer of pollutants, the functional diversity of the ecosystems, and poor harmonization among the policies and regulations in different countries for organic farming.